Development of Competency-Based Arabic Language Curriculum in Traditional Islamic Boarding Schools - Kholis, Nur; Mustofa, M. Arif (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This study aims to determine the development of Maharoh-based Arabic language curriculum (competence) in Traditional Islamic Boarding Schools. The rapid development of today's times makes people want that even though a student is in a pesantren, his Arabic language skills must also develop, namely being able to speak Arabic passively and actively. Based on this, the reform of the Arabic learning system and curriculum in Islamic boarding schools is an urgent need, so that Islamic boarding schools can keep pace with the rapid development of science, technology, and information. This research uses a qualitative approach in the form of a case study. With a qualitative approach in the form of a case study, the important findings in this study are the results of curriculum development in curriculum components consisting of; The components of the objectives and development are contained in the objectives of learning Arabic which include the abilities that must be possessed by students in Arabic language skills, namely maharoh (competence) istima, maharoh (competence) kalam, maharoh (competence) qiroah and maharoh (competence) kitabah. The development of content/material components is found in materials related to daily activities. At the same time, the development of process components is found in the use of various strategies and methods by adapting to the material being studied. Developing an evaluation component involves conducting varied evaluations and adjusting the character of the material being taught.